Rosiglitazone up‐regulates glial fibrillary acidic protein via HB‐EGF secreted from astrocytes and neurons through PPARγ pathway and reduces apoptosis in high‐fat diet‐fed mice. Issue 5 (7th December 2018) - Kushwaha, Rajesh; Mishra, Juhi; Gupta, Anand Prakash; Gupta, Keerti; Vishwakarma, Jitendra; Chattopadhyay, Naibedya; Gayen, Jiaur Rahaman; Kamthan, Mohan; Bandyopadhyay, Sanghamitra
Abstract : Abstract: The anti‐diabetic drug and peroxisome proliferator‐activated receptor‐gamma (PPARγ) agonist, rosiglitazone, alters astrocyte activation; however, its mechanism remains less‐known. We hypothesized participation of epidermal growth factor receptor (EGFR), known to control astrocyte reactivity. We first detected that rosiglitazone promoted glial fibrillary acidic protein (GFAP) expression in primary astrocytes as well as the mouse cerebral cortex, associated with increased EGFR activation. Screening for EGFR ligands revealed a rosiglitazone‐mediated increase of heparin‐binding epidermal growth factor (HB‐EGF) in astrocytes, resulting in HB‐EGF release into culture medium and mouse cerebrospinal fluid too. Treatment with HB‐EGF‐siRNA and EGFR inhibitors showed that the rosiglitazone‐induced HB‐EGF and p‐EFGR were interdependent, which participated in GFAP increase. Interestingly, we observed that rosiglitazone could induce cellular and secreted‐HB‐EGF in neurons also, contributing toward the activated EGFR‐induced GFAP in astrocytes. Probing whether these effects of rosiglitazone were PPARγ‐linked, revealed potential PPARγ‐responsive elements within HB‐EGF gene. Moreover, gel‐shift, site‐directed mutagenesis, chromatin‐immunoprecipitation and luciferase‐reporter assays demonstrated a PPARγ‐dependent HB‐EGF transactivation. Subsequently, we examined effects of rosiglitazone in a high‐fat diet‐fed diabetes mouse model, and supporting observations in the normal cortical cells, identified a rosiglitazone‐induced GFAP, astrocyte and neuronal HB‐EGF and secreted‐HB‐EGF in the cerebral cortex of diabetic mice. Moreover, assessing relevance of increased HB‐EGF and GFAP revealed an anti‐apoptotic role of rosiglitazone in the cerebral cortex, supported by a GFAP‐siRNA as well as HB‐EGF‐siRNA‐mediated increase in cleaved‐caspase 3 and 9 levels in the rosiglitazone‐treated astrocyte–neuron coculture. Overall, our study indicates that rosiglitazone may protect the brain, via a PPARγ‐dependent HB‐EGF/EGFR signaling and increased GFAP. Abstract : The anti‐diabetic drug rosiglitazone, promoted GFAP expression in astrocytes, associated with increased EGFR activation. Rosiglitazone induced a PPARγ‐dependent expression of the EGFR ligand, HB‐EGF, in astrocytes and neurons, contributing towards the activated EGFR‐induced GFAP. Similar findings were observed in the diabetic mice. Additionally, increased HB‐EGF and GFAP resulted in an anti‐apoptotic role of rosiglitazone within the brain. Overall, our study indicates that rosiglitazone may protect the brain, via a PPARγ‐dependent HB‐EGF/EGFR signalling and increased GFAP.